2023
DOI: 10.35508/jom.v16i2.9929
|View full text |Cite
|
Sign up to set email alerts
|

THE EXISTENCE AND SURVIVAL STAGE IN SMEs SUSTAINABILITY TRANSFORMATION

Abstract: The purpose of this study is to explore SMEs’ proactive approach towards sustainability transformation, especially in the existence and the survival stage, what are the challenges and opportunities that come with each stage of a company's existence can help SMEs plan for their sustainability transformation in a way that is appropriate for their current stage of development. The interpretivism paradigm is used in this study. This research involves collecting qualitative data through the interview method. Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Research has shown that SMEs face various challenges and opportunities in their sustainability transformation. The proactive approach toward sustainability transformation is crucial for SMEs, especially in the existence and survival stages [17]. Factors such as digitalization, business strategy, and competitive advantage have been found to impact the sustainability of SMEs, including women-owned businesses [18].…”
Section: Entrepreneurial Marketing and Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that SMEs face various challenges and opportunities in their sustainability transformation. The proactive approach toward sustainability transformation is crucial for SMEs, especially in the existence and survival stages [17]. Factors such as digitalization, business strategy, and competitive advantage have been found to impact the sustainability of SMEs, including women-owned businesses [18].…”
Section: Entrepreneurial Marketing and Sustainable Developmentmentioning
confidence: 99%
“…In terms of innovation orientation, immigrants in this phase not only continue to absorb new knowledge but also integrate personal experience for business development. Compared to the previous stage, immigrants now have the capability to compile business and mainstream societal preferences, thereby constructing a knowledge structure infused with personal characteristics, systematically applying this structure to seize business opportunities [5,17].…”
Section: Growth Expansion Phase: the Stage With The "Objective Of Ent...mentioning
confidence: 99%